Lokālās vēstures integrācija sociālo zinību un vēstures mācību procesā 5. klasē - Ozoliņa, Aiva (Latvijas Universitāte, 2025)
Bachelor`s work theme is Integration of Local History into the Social Studies and History Curriculum in Grade 5. The aim of the thesis is to theoretically substantiate and empirically evaluate how the integration of local history into the teaching process can enhance students’ understanding of historical and societal processes, foster identity awareness, and strengthen their sense of belonging. The study is based on the competence-based education approach as defined by SKOLA2030, as well as on current pedagogical insights concerning meaningful learning content, taking into account the developmental characteristics of the respective age group. The theoretical part analyses the concept and significance of local history in the educational process, age-specific developmental features of Grade 5 students, and modern teaching methods that promote student engagement and inquiry-based learning. The empirical part presents an action research study conducted in a Grade 5 classroom, where various teaching tasks were implemented. These tasks linked students’ everyday experiences with local historical events and notable figures. To collect data, the research employed student and teacher surveys, observations, and student reflections. The findings demonstrate that the integration of local history into social studies and history lessons enhances students’ comprehension of historical and social phenomena, develops research skills, and strengthens their connection to their local community. The thesis offers practical recommendations for teachers and confirms that local history can serve as a valuable resource for contextualizing curriculum content. Keywords: local history, social studies, history, Grade 5, action research, SKOLA2030, identity, belonging.

Bakalaura darba tēma ir “Lokālās vēstures integrācija sociālo zinību un vēstures mācību procesā 5. klasē”. Darba mērķis ir teorētiski pamatot un empīriski izvērtēt, kā lokālās vēstures integrēšana mācību procesā var veicināt skolēnu izpratni par vēstures un sabiedrības norisēm, identitātes apzināšanos un piederības sajūtas stiprināšanu. Pētījums balstīts uz kompetencēs balstīta izglītības pieeju SKOLA2030 un aktuālām pedagoģiskām atziņām par jēgpilnu mācību saturu, ņemot vērā arī vecumposma īpatnības. Teorētiskajā daļā analizēti lokālās vēstures jēdziens un nozīme mācību procesā, vecumposma attīstības īpatnības un mūsdienīgas mācību metodes, kas sekmē skolēnu iesaisti un izziņu. Empīriskajā daļā veikts darbības pētījums 5. klasē, aprobējot vairākus mācību uzdevumus, kas sasaista skolēnu ikdienas pieredzi ar vietējās vēstures notikumiem un personībām. Datu ieguvei izmantotas skolēnu un skolotāju aptaujas, to analīze, novērojumi un skolēnu refleksijas. Pētījuma rezultāti liecina, ka lokālās vēstures integrācija sociālo zinību un vēstures mācību stundās veicina skolēnu izpratni par vēstures un sabiedrības procesiem, attīsta pētnieciskās prasmes un stiprina piederību savai kopienai. Darbs piedāvā praktiskus ieteikumus skolotājiem un apliecina, ka lokālā vēsture var kalpot kā nozīmīgs resurss mācību satura kontekstualizācijai. Atslēgas vārdi: lokālā vēsture, sociālās zinības, vēsture, 5. klase, darbības pētījums, SKOLA2030, identitāte, piederība.
Integration of Local History in the Teaching and Learning Process of Social Sciences and History in Grade 5
Keywords: Izglītības zinātnes; lokālā vēsture; sociālās zinības un vēsture; piederība; 5. klase; darbības pētījums